Réflexions autour de la conservation-restauration d’une œuvre aux coléoptères de Jan Fabre, Vleesklomp - Ingrid Wydler (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The following article is about the treatment of Jan Fabre’s coleopteran piece of art. The artist’s work is presented throughout this text, witch deals with conservation issues of coleopteras and treatment chosen for the artwork.